Corrosion of high purity Mg, Mg2Zn0.2Mn, ZE41 and AZ91 in Hank’s solution at 37°C - Zainal Abidin, Nor Ishida; Atrens, Aleks D.; Martin, Darren; Atrens, Andrej (Elsevier, 2011)
The CO2 partial pressure required to maintain a synthetic body fluid (SBF) at a constant pH, based on the initial bicarbonate concentration, was evaluated to be 0.013atm for Hank's solution and 0.083atm for SBF27. Corrosion of high purity Mg and three Mg alloys in Hank's solution was studied using hydrogen evolution, weight loss and Tafel extrapolation. The solution pH was maintained constant by CO2. There was initially an incubation period with a low corrosion rate, a period of increasing corrosion rate, and subsequently steady state corrosion. Some hydrogen dissolved in the Mg metal. © 2011 Elsevier Ltd.